Analyse phytochimique et l’effet anti-inflammatoire in vitro de l’algue rouge Sphaerococcus coronopifolius. - Izerouel, Chahinez (My University, 2022)
Aquatic environments contain organisms rich in compounds endowed with biological activities presenting an immense resource of new compounds with significant capacities; among these organisms are algae which are a possibly rich source of bioactive compounds. In this present work we evaluated the extraction rate, phytochemical screening and the rate of phenolic compounds, as well as the in vitro anti-inflammatory activity of methanolic extract of the seaweed Sphaerococcus coronopifolius which is tested with two different methods: evaluation of its protective properties against thermal denaturation of BSA albumin and against heat-induced hemolysis of red blood cells. The results indicate a yield of crude extract is 1.6%. Phytochemical screening revealed the presence of some bioactive substances: alkaloids, glycosides and saponins. The quantification of total polyphenols and flavonoids gave a high value in total polyphenols 582.78 Ec μg EAG / mg of extract compared to that of total phenols 70.544 μg EQ / mg extract. However, the results of the anti-denaturing activity of the proteins of this species are IC50=8.51±1.84μg /ml. On the other hand, the results obtained during the anti-hemolytic test by heat gave IC50=71.39±0.21μg/ml. Sphaerococcus coronopifolius species which is rich in bioactive substances has antiinflammatory activity
Keywords: Sphaerococcus coronopifolius; phytochemical screening; total polyphenols; total flavonoids; in vitro anti-inflammatory activity